A solution of transient rolling contact with velocity dependent friction by the explicit finite element method. Issue 4 (13th June 2016) - Zhao, Xin; Li, Zili
Abstract : Purpose: – The purpose of this paper is to develop a numerical approach to solve the transient rolling contact problem with the consideration of velocity dependent friction. Design/methodology/approach: – A three dimensional (3D) transient FE model is developed in elasticity by the explicit finite element method. Contact solutions with a velocity dependent friction law are compared in detail to those with the Coulomb's friction law (i.e. a constant coefficient of friction). Findings: – The FE solutions confirm the negligible influence of the dependence on the normal contact. Hence, analysis is focussed on the tangential solutions under different friction exploitation levels. In the trailing part of the contact patch where micro-slip occurs, very high-frequency oscillations are excited in the tangential plane by the velocity dependent friction. This is similar to the non-uniform sliding or tangential oscillations observed in sliding contact. Consequently, the micro-slip distribution varies greatly with time. However, the surface shear stress distribution is quite stable at different instants, even though it significantly changes with the employed friction model. Originality/value: – This paper proposes an approach to solve the transient rolling contact problem with the consideration of velocity dependent friction. Such a problem was usually solved in the literature by the simplified contact algorithms, with which detailed contact solutions could not be obtained, or with the assumption of steady rolling.